Pengaruh Environmental Performance dan Leverage terhadap Pengungkapan Islamic Social Reporting dengan Profitabilitas sebagai Variabel Intervening pada Perusahaan yang Terdaftar di Jakarta Islamic Index Tahun 2020–2022 - Rostina, Delvia (Jurnal KIAFE, 2024)
This study examines the effects of environmental performance and leverage on Islamic Social Reporting disclosure, with profitability as an intervening variable, in companies listed on the Jakarta Islamic Index during the 2020–2022 period. The study employs a quantitative approach using secondary data obtained from annual reports and financial statements published by the Indonesia Stock Exchange and the respective companies. The sample was selected through purposive sampling and consisted of 20 companies, resulting in 60 firm-year observations. Data were analyzed using WarpPLS version 7.0. The results show that environmental performance has a positive and significant effect on Islamic Social Reporting disclosure, while leverage has no significant effect. Environmental performance and leverage do not have significant effects on profitability, whereas profitability has a positive and significant effect on Islamic Social Reporting disclosure. Furthermore, profitability is unable to mediate the effects of environmental performance and leverage on Islamic Social Reporting disclosure. The model explains 26% of the variation in Islamic Social Reporting disclosure.